Relationships between Oak powdery mildew incidence and severity and commensal fungi. Issue 2 (14th August 2015) - Topalidou, E. T.; Shaw, M. W.
Summary: Oak ( Quercus robur ) powdery mildew is a common and damaging fungal disease. In a local survey at Reading, UK, oak powdery mildew was common on trees of all height classes but was most common on trees of 3–9 m. A variety of other fungal species were commonly found growing in association with oak powdery mildew colonies. The abundance of such fungi was estimated through stratified sample surveys for 2.5 years. The taxa most commonly associated with oak powdery mildew were Acremonium sp., Trichoderma sp ., Ampelomyces/Phoma sp. and Leptosphaerulina australis . Nearly 90% of mildew colonies were associated with L. australis, which is not generally considered as a mycoparasite or antagonist, in contrast with the other three fungi. Abundance varied between June and October surveys. Acremonium sp. abundance was greater in summer samplings, whereas L. australis and Trichoderma sp. abundances were greater in autumn samplings. Ampelomyces/Phoma sp. was never observed in the absence of powdery mildew. Relationships between the mildew‐associated fungi and oak powdery mildew appeared curved and differed significantly between sampling years. L. australis was positively correlated with the other three associated fungi studied when powdery mildew was also present. The variety and high population densities of the mildew‐associated fungi suggest that they may be important in determining the final density of oak mildew and the damage caused by it.